2021
DOI: 10.5539/ies.v14n5p135
|View full text |Cite
|
Sign up to set email alerts
|

The Relationships Between Internet Addiction, Social Appearance Anxiety and Coping with Stress

Abstract: The purpose of this study is to examine internet addiction in terms of social appearance anxiety and strategies for coping with stress. The dependent variable of the research is internet addiction, and its independent variables are social appearance anxiety and strategies for coping with stress. The study group of the research consists of 481 undergraduate and postgraduate students as 318 women (66.1%) and 163 men (33.9%). In order to collect data in the study, Short Version of Young’s Internet Addic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…In parallel with this finding, several studies showed that there was a strong positive relationship between self-presentation or body image control and frequency of social media use (Boursier & Manna, 2019;Gioia et al, 2020). Doğan and Çolak (2016) draw attention to the fact that adolescents with high social appearance anxiety can express themselves more easily by choosing social media rather than physical-social environments (also see Ayar et al, 2018;Baltacı et al, 2021;Brown & Tiggemann, 2016;Holland & Tiggemann, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…In parallel with this finding, several studies showed that there was a strong positive relationship between self-presentation or body image control and frequency of social media use (Boursier & Manna, 2019;Gioia et al, 2020). Doğan and Çolak (2016) draw attention to the fact that adolescents with high social appearance anxiety can express themselves more easily by choosing social media rather than physical-social environments (also see Ayar et al, 2018;Baltacı et al, 2021;Brown & Tiggemann, 2016;Holland & Tiggemann, 2016).…”
Section: Discussionmentioning
confidence: 82%
“…Social appearance anxiety, on the other hand, is a type of anxiety defined as the fear of being negatively evaluated or rejected by others because of one's physical appearance [3][4][5][6][7]. People who experience social appearance anxiety usually hold a negative perception of their body and appearance [8][9][10][11], and they frequently try to camouflage the features or the body parts they dislike [8]. In addition, they prefer minimum physical contact and instead use internet communication, which involves less risk of exposure, as well as offering an easier way to manipulate their image and overall appearance [2].…”
Section: Introductionmentioning
confidence: 99%
“…The internet and social media contribute to many types of social comparison, creating an ideal body image. On the internet, people are exposed to a multitude of images that may be considered the most suitable as a benchmark for social appearance [8]. Many of them are idealized and associated with negative feelings about the body and the person's desire to change their weight and body shape [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They also try to hide their body or parts of their body that they do not like. The social, academic and professional sectors can be negatively affected by social appearance anxiety ( Baltaci et al ., 2021 ). Social appearance anxiety includes a more complete concept of physical appearance, extending from the general physical characteristics associated with physiques such as height, weight and muscle structure to more personal characteristics such as skin, hair, face shape and size of features ( Argon, 2014 ), therefore, the term broader as it includes both general appearance problems and physique concerns.…”
Section: Introductionmentioning
confidence: 99%